Democratic Republic of the Congo : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for the Democratic Republic of the Congo. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Democratic Republic of the Congo's (DRC) Request for Disbursement Under the Rapid Credit Facility (RCF). DRC is experiencing a severe shock as a result of the Covid-19 pandemic. The short-term economic outlook has deteriorated quickly due to the fall of minerals' prices and the impact of needed containment and mitigation measures. The IMF's emergency financial support under the RCF is expected to address DRC's urgent balance of payments needs while supporting this temporary fiscal loosening. Additional assistance from other development partners is expected to close the remaining external financing gap and ease budget financing needs. The authorities' commitment to publish monthly audits of coronavirus disease 2019 related expenditures is welcome, to ensure transparency in the use of public funding. The implementation of the policies and structural reforms to which the authorities committed under the staff-monitored program agreed in December remains key to ensuring macroeconomic stability and restoring sustained inclusive growth. These include strengthening transparency and governance in the fiscal and mining sectors, boosting revenue mobilization, maintaining financial stability, and halting central bank financing of the deficit.